Medosebni odnosi in zdravje v okviru soseske in skupnosti - Kavčič, Matic (Teorija in praksa, 2016)
People living in neighbourhoods have a range of interpersonal relationships. In this article, we want to examine whether the characteristics of people's interpersonal relationships in a neighbourhood and the characteristics of their health are related. We investigated this problem in a study of the population of residents of multi-apartment buildings in Ljubljana's neighbourhoods. Empirical data were gathered from a survey of neighbourly relations. The findings of bivariate analyses and multiple linear regression show that already known factors such as the financial situation of the household and age remain the most important predictors of health. However, we found that certain aspects and characteristics of interpersonal relationships have a significant impact on the health of the inhabitants of these residential communities. In particular, we examined empowerment, which proved to be an important factor and should be given more research attention in the future.
Keywords: Health; Ljubljana (Slovenia; Mestna občina); Ljubljana (Slovenija; mestna občina); Local communities; Lokalne skupnosti; medosebni odnosi; Neighbourhood; opolnomočenje; Soseska; Zdravje